(untitled) (Research, Society and Development, 2023)
This is a descriptive exploratory study with a qualitative approach, aiming to reveal the perception of primiparous mothers about their experience of breastfeeding, to identify the understanding of primiparous mothers about the importance of breastfeeding and the consequence of early weaning, and to propose a plan of care for primigravidae mothers with a view to equipping the nursing team in order to reduce early weaning. The research was carried out with 30 women, nursing mothers for the first time, in a virtual environment, via the Google Meet videoconference platform, recorded, lasting approximately thirty minutes. The analysis of the information was carried out using the technique of content analysis according to Bardin (2016), from which two categories emerged: Difficulties facing breastfeeding for primiparous mothers and challenges facing breastfeeding for primiparous mothers, which were divided, respectively, into five and four subcategories. It was evident that, although all research participants reported having prenatal care, there are many gaps in knowledge about breastfeeding among primigravidae mothers, demonstrating flaws in the process of guidance and professional assistance in all stages of motherhood. Finally, based on the main difficulties and challenges in relation to breastfeeding, from the perspective of the research participants, nursing diagnoses and a care plan were listed in order to equip the nursing team, reduce the numbers referring to early weaning and increase rates of adherence to exclusive breastfeeding and ensure a better quality of child health.